The extension of the principle of precaution across obligatoryـ recommendedـ and reprehensible acts - Ahmed Jamil Mhana (Islamic Sciences Journal, 2025)
The research addresses precaution in Islamic jurisprudence regarding its conceptـ applications. It shows that precaution protects religion and honorـ supported by evidence from the Qur’anـ Sunnahـ and the Companions. Scholars defined it as avoiding the prohibited or neglecting the obligatory when in doubt. The study highlights the scholarly disagreement: most consider it a legal principleـ while Ibn Hazm rejected it if based on a fatwa without evidence but accepted it as personal piety. Precaution is bound by conditions: no explicit textـ no neglect of Sunnah or commission of the forbiddenـ and no matters of creed. Its objectives are to safeguard rulingsـ avoid doubtsـ and clear the conscience. Applications include: obligatory when ensuring duties or avoiding prohibitions; recommended when aiding piety or avoiding disputes; and reprehensible when causing hardship or obsessive thoughts. The study concludes that precaution is a valid principle if practiced with balanceـ serving to preserve religion and avoid doubtful matters.